Argument Misguided and Divisive: A Reply to DeYoung, Howley & Theobald (1995) - Joan Lipsitz (Journal of Research in Rural Education, 1995)
In their article, "The Cultural Contradictions of Middle Schooling for Rural Community Survival," DeYoung, Howley, and Theobald (1995) argue that "middle schooling puts the presumed prerogative of child development ahead of social, cultural, and historical priorities" (p. 25). In so doing, middle schools typically overlook existing linkages between schools and their social and cultural contexts" (p. 25), thereby threatening the integrity of rural communities. By making this argument, the authors pit the needs of children against the common good.